Efeito do cultivo de plantas leguminosas sobre a população de nematoides em solos naturalmente infestados - Obici, Luciana Villanova (2009)
The aim of this study was to evaluate Arachis pintoi, Canavalia ensiformis and Stylosanthes Campo Grande legumes cultivation over nematodes in naturally infested soils with a history of sugarcane crop. For this, naturally infested silt loam and clay loam soils were distributed into pots being transplanted two maize seedlings in order to facilitate nematode multiplication. After 60 days, plants aerial part was discarded and initial nematode population determined by assessing nematodes number (in the soil and roots). Legume seedlings were transplanted into the pots where remained for three or four months, analyzing again, the same nematodes populations. Maize was used as susceptible control. Finally, two sugarcane seedlings were transplanted into each pot, in order to assess the residual effect of the plants over nematodes in soil, by using the same parameters. Pratylenchus zeae and Helicotylenchus dihystera were present in analyzed samples. The results obtained showed that, regardless of soil type and cultivation time spent in pot, the three legume species were efficient for controlling P. zeae, with an outstanding effect even after 120 days of subsequent sugarcane cultivation. Canavalia ensiformis allowed increasing of H. dihystera population, whereas the other legumes caused its reduction. The conducted work allowed concluding that the three tested legumes may be used to P. zeae control. However, more studies need to be performed in relation to its effect, and in particular for C. ensiformis, over H. dihystera